Social Robots as Co-Therapists in Autism Therapy Sessions: A Single-Case Study - Ioannou, Andri; Kartapanis, Iosif; Zaphiris, Panayiotis (My University, 2015)
This study aimed to explore the potential value of a humanoid robot, NAO, in assisting the therapist during therapy sessions with children in the autism spectrum (ASD). We report findings from a single case, a 10-year old boy, Joe (pseudonym), diagnosed with high functioning ASD. The intervention was conducted in four consecutive therapy sessions with Joe during which Joe played the “Animals Game” with NAO and the therapist. In this game, NAO asked Joe to find a specific animal from a deck of cards. Numerical data demonstrated Joe’s progress across sessions in terms of discriminating the animals from images and learning the animals in English. Additionally, based on qualitative observations, we have evidence of Joe becoming more independent from session to session, initiating interaction with NAO, directing his gaze and expressing affective feelings.
Keywords: NAO; Humanoid robot; Autism; ASD; Therapy; Interaction; Social robots; Social behavior